Effects of Eco-Drive Education on the Reduction of Fuel Consumption and CO2 Emissions - Barić, Danijela; Zovak, Goran; Periša, Marko (Promet - Traffic&Transportation, 2013)
Sustainable mobility is the basic and long-term goal of the traffic policy. Eco-driving represents one of 40 measures that should by 2050 contribute to 60% of traffic-generated emission reduction. The paper presents the significance of educating the drivers about eco-driving as well as eco-drive training with the aim of reducing fuel consumption and CO2 emission. During research the drivers were tested in three cycles, prior to education, immediately following the education and eco-training and three months after the eco-training. The analysis of the results shows that driving according to eco rules allows fast and efficient reduction of fuel consumption and CO2 emissions, which means at the same time also the need to systemically educate the drivers about the eco-driving at specialized educational centres which is for the moment absent in the Republic of Croatia.